2011
DOI: 10.1016/j.na.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic Ptolemy spaces and fixed points

Abstract: We prove that geodesic Ptolemy spaces with a continuous midpoint map are strictly convex. Moreover, we show that geodesic Ptolemy spaces with a uniformly continuous midpoint map are reflexive and that in such a setting bounded sequences have unique asymptotic centers. These properties will then be applied to yield a series of fixed point results specific to CAT(0) spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…However, Busemann convexity implies the CAT(0) condition in the setting of Ptolemy spaces [20]. Other properties of geodesic Ptolemy spaces in connection to metric fixed point theory can be found in [18,19].…”
Section: Some Examples Of Metric Spaces With the Betweenness Propertymentioning
confidence: 99%
“…However, Busemann convexity implies the CAT(0) condition in the setting of Ptolemy spaces [20]. Other properties of geodesic Ptolemy spaces in connection to metric fixed point theory can be found in [18,19].…”
Section: Some Examples Of Metric Spaces With the Betweenness Propertymentioning
confidence: 99%
“…In recent years, CAT(0) spaces have attracted the attention of many authors as they have played a very important role in different aspects of geometry ( [12]). Kirk [18,19] showed that a nonexpansive mapping defined on a bounded closed convex subset of a complete CAT(0) space has a fixed point.…”
Section: Introductionmentioning
confidence: 99%
“…Now we introduce the concept of model spaces M n κ . For more details on these spaces, the reader is referred to [4,14]. Let n ∈ N .…”
Section: Preliminariesmentioning
confidence: 99%
“…Taking {ν n = 0}, ζ = t, t ≥ 0, then (1.3) can be written as In recent years, CAT(0) spaces (the precise definition of a CAT(0) space is given below) have attracted the attention of many authors because they have played a very important role in different aspects of geometry [4]. Kirk [5,6] showed that a nonexpansive mapping defined on a bounded closed convex subset of a complete CAT(0) space has a fixed point.…”
Section: Introductionmentioning
confidence: 99%